Mindfulness at Work: A Bibliometric Analysis of Key Authors, Themes, and Trends - Thapa, Bharat; Gurung, Amrit Kumar; Neupane, Dhruba Kumar; Timalsena, Chiranjibi; Neupane, Avinash; Nyaupane, Netra Prasad; Chalise, Bhola Nath (NPRC Journal of Multidisciplinary Research, 2024)
Background: Mindfulness in the workplace has gained significant attention for its potential to enhance well-being, reduce stress, and improve productivity. As interest in workplace mindfulness has grown, a need arises to systematically analyze the influential studies, key authors, themes, and trends shaping this field. Objectives: This study aims to map the intellectual landscape of "mindfulness at work" through a bibliometric analysis, identifying key contributions, collaboration networks, thematic clusters, and publication trends over time. Methods: Utilizing data from Lens.org, we conducted a bibliometric analysis using VOSviewer and WordSift tools to examine co-authorship, keyword co-occurrence, and citation networks, as well as keyword frequency and thematic trends. Findings: The analysis identifies central figures such as Jochen Reb and Christopher J. Lyddy and highlights prominent themes including well-being, stress management, and engagement, with a peak in publication interest around 2019. The study also reveals isolated research clusters, suggesting limited interdisciplinary integration within the field. Conclusion: While mindfulness research at work is growing, opportunities exist for deeper cross-disciplinary collaboration and broader integration of themes. Novelty: This study provides a comprehensive overview of the field’s development, offering insights into emerging trends, key influencers, and areas for future exploration, making it a valuable resource for researchers, practitioners, and policy-makers interested in advancing workplace mindfulness.